Making a Living in Ottoman Anatolia - Boyar, Ebru,; Fleet, Kate, (Middle East and Islamic Studies E-Books Online, Collection 2021, ISBN: 9789004441286., 2021)
Centred on the socio-economic life of Ottoman Anatolia, this volume examines aspects of production, local and international trade, consumption and the role of the state, both at a local and a central level. Based on a wide array of data and adopting a variety of approaches, chapters range from the macro to the micro, from the overview of Anatolian economic resources to the in-depth examination of the petition language of provincial economic actors. Making a Living in Ottoman Anatolia thus offers the reader an entrée into the rich and varied socio-economic life of a central region of the Ottoman empire. Contributors are Marc Aymes, Ebru Boyar, Metin Coşgel, Suraiya Faroqhi, Kate Fleet, Elena Frangakis-Syrett, Yonca Köksal, Mehmet Öz, Mehmet Polatel and Sadullah Yıldırım.